Materials Mix and Yield Variances: A Suggested Improvement. - Wolk, Harry I.; Hillman, A. Douglas (The Accounting Review, 1972)
The article suggests an improvement in the accounting field of mix variance. Mix variances arise when factor input combinations of raw materials or grades of labor differ in composition from the standard mix. It is also used to analyze sales or contribution margin when actual mix differs from budgeted mix. The primary intention is to propose a different structure of raw material variances where the standard mix is intentionally abandoned in the short-run due to raw material price changes, causing a different combination to be optimal. Criticism of the mix and yield variances and proposed recasting for the above situation follows the first portion of the paper which is devoted to the planning function. In terms of the planning-performance- control cycle, if output can be attained with different mixes of materials inputs, decisions can be implemented by means of mathematical models such as linear programming. In conclusion, it is apparent that the traditional materials mix and yield variances suffer from an advanced case of technological obsolescence.